Responsible Research and Innovation in Science Education: The Solution or The Emperor’s New Clothes? - Lundström, Mats (2017)
Abstract The European Commission has for the past 10 years emphasised the importance of “Responsible research and innovation” (RRI). RRI is an approach that anticipates and assesses potential implications and societal expectations with regard to research and innovation, with the aim to foster the design of inclusive and sustainable research and innovation. Despite efforts to support RRI projects, however, little attention has been given to RRI in science education and science education research over this period. This article problematises the concept RRI and its relation to some of the key concepts in science education, comparing and discussing it in relation to scientific literacy, nature of science and socioscientific issues. The meeting between scientists and students is emphasised as a key issue to address, if RRI is to be regarded as an important part of science education. Resumo A Comissão Europeia tem enfatizado nos últimos 10 anos a importância da Investigação e Inovação Responsáveis (IIR). A IIR é uma abordagem que antecipa e avalia as potenciais implicações e as expectativas societais no que diz respeito à investigação e inovação, com o objetivo de fomentar o desenvolvimento de uma investigação e inovação inclusiva e sustentável. No entanto, apesar dos esforços para apoiar os projetos de IIR, durante este período pouca atenção foi dada à IIR na educação em ciências e na investigação em educação em ciências. Este artigo problematiza o conceito de IIR e a sua relação com alguns dos conceitos-chave da educação em ciências, comparando-o e discutindo-o relativamente à literacia científica, à natureza da ciência e às questões sociocientíficas. O encontro entre cientistas e estudantes é enfatizada como uma questão-chave a abordar, se a IIR for considerada uma parte importante da educação em ciências.